Learning through blog writing embracing the technology - Normaliza Abd. Rahim (Penerbit Universiti Malaysia Terengganu, 2014)
[This book] is the first text to stress the importance of understanding and celebrating difference as a means to becoming a more effective way of using the technology ini teaching and learning. This text targets both mainstream language students and non-traditional students who range widely in age, ethinicity, race, religion, social roles and socio-economu status. This text describes basic theory in learning through blog writing, non-technical terms and offers students and educators an abundance of opportunities to analyze, understand, practice, and apply skills to real-life situations.